Impro : Improvisation and the Theatre. - Johnstone, Keith (Taylor and Francis, 2012)
Keith Johnstone's involvement with the theatre began when George Devine and Tony Richardson, artistic directors of the Royal Court Theatre, commissioned a play from him. This was in 1956. A few years later he was himself Associate Artistic Director, working as a play-reader and director, in particular helping to run the Writers' Group. The improvisatory techniques and exercises evolved there to foster spontaneity and narrative skills were developed further in the actors' studio then in demonstrations to schools and colleges and ultimately in the founding of a company of performers, called The.